ANALISIS KESIAPAN BELAJAR MATEMATIKA SISWA SECARA BLENDED LEARNING DALAM MASA TRANSISI - Lintang Ega Shavira; Leana Iramaya Phasa; Muhammad Muchlishin; Sumbaji Putranto (Pendidikan Matematika UNIMOR, 2022)
This research was conducted to see the readiness of students in implementing blended learning mathematics in the current transition period. Blended learning was chosen as a way of learning for students with a mixture of online and offline. This was implemented after the community evenly carried out a vaccination program from the government to prevent the Covid-19 virus. The readiness of students to take part in learning mathematics is judged by how students fill out questionnaires in the Google Form that we distribute. Students fill in several questions in the form of short questions, multiple choice with two options and several Likert scales that we have made. The method used in this study is a qualitative descriptive method using a questionnaire technique. Respondents in this study were students at one of the Madrasah Aliyah in Wonosari, Gunung Kidul Regency, Yogyakarta who were selected randomly. The result of this study indicate that students can accept learning with the Blended Learning method in this transition periodperiod with 50% no problem and 35,7% ready in this learning. However, as many as 64,3% of students want offline learning and 7,1% want online learning. Then the remaining 28,6% of students want Blended Learning.